Epizyotomi üzerine sistematik inceleme ve meta-Aanaliz çalışması - Can Ravera, Burcu (My University, 2023)
Amaç: Epizyotominin maternal sağlık üzerine etkilerini, ağrıya yönelik girişimleri ve epizyotomi insizyonunda kullanılan sütür, materyal ve tekniklerin maternal sonuçlara etkisini değerlendirmek amacıyla yapılmıştır. Gereç ve Yöntem: Çalışmada sistematik inceleme ve meta-analiz kullanılmıştır. Araştırmaya EbscoHost CINAHL, Medline, Science Direct, Science Citation Index, Springer Link, Ovid, BMJ Journals, Cochrane Central Register of Controlled Trials, Networked Digital Library of Theses & Dissertation ve Proquest, ULAKBİM, YÖK Ulusal Tez Merkezi ve Türkiye Klinikleri veri tabanlarında “episiotomy”, “epizyotomi” ve bununla ilişkili terimler kullanılarak 1980- 2022 tarih aralığı ve İngilizce Türkçe dil sınırlaması yapılarak toplam 23267 yayına ulaşılmıştır. Bulgular: Çalışmaya 75 araştırma dahil edilmiştir. Yapılan meta- analizlerde uygulanan epizyotominin istatistiksel olarak anlamlı bir şekilde kanamayı (OR:2,21 %95 CI [1,77- 2,76]), postpartum ağrıyı (OR:6,11 %95 CI [4,11- 9,08]), obstetrik anal sifinkter yaralanmalarını (OR: 1,54 %95 CI [1,23- 1,92]) ve disparoniyi (OR: 1,76 %95 CI [1,15- 2,71)) arttırdığı saptanmıştır. Postpartum soğuk (MD: -1,24) ve lavanta kullanımının (MD: -0,63) ağrı skorlarını azaltıcı bir etkisi olduğu görülmüştür. Devamlı sütür tekniği ve hızlı emilen sütür materyalinin maternal sonuçlarının daha iyi olduğu belirlenmiştir. Sonuç: Yapılan meta- analizler sonucunda epizyotomi maternal morbiditeyi (kanama, ağrı, disparoni, obstetrik anal sifinkter yaralanmaları) arttırdığı için epizyotomi uygulamadan önce gebeler risk faktörleri açısından kapsamlı değerlendirilmelidir.

Objective: It was conducted to evaluate the effects of episiotomy on mothernal health, interventions for pain, and the effects of sutures, materials and techniques used in episiotomy incisions on mothernal outcomes Material and Methods: Systemic Review and meta-analysis were used in the study. The research was conducted by searching the databases EbscoHost CINAHL, Medline, Science Direct, Science Citation Index, Springer Link, Ovid, BMJ Journals, Cochrane Central Register of Controlled Trials, Networked Digital Library of Theses & Dissertation, Proquest, ULAKBİM, YÖK National Thesis Center, and Turkish Clinics, using the terms episiotomy, epizyotomi, and related terms, a total of 23267 publications were reached by limiting the date range of 1980 to 2022 and English and Turkish languages. Outcomes: 75 studies were included in the study. In the meta-analyses, episiotomy applied statistically significantly reduced bleeding (OR: 2.21 95% CI [1.77- 2.76]) and postpartum pain (OR: 6.11 95% CI [4.11- 9, 08]), was found to increase obstetric anal sphincter injuries (OR: 1.54 95% CI [1.23- 1.92]) and dyspareunia (OR: 1.76 95% CI [1.15- 2.71)). Postpartum cold (MD: -1.24) and lavender use (MD: -0.63) were found to have a reducing effect on pain scores. It has been determined that the continuous suture technique and rapidly absorbable suture material have better maternal outcomes. Conclusion: As a result of the conducted meta-analyses, episiotomy has been found to increase maternal morbidity (hemorrhage, pain, dyspareunia, obstetric anal sphincter injuries) pregnant women should be comprehensively evaluated in terms of risk factors before performing episiotomy.
Systemic review and meta-analysis on episiotomy
Keywords: Doğum hemşireliği; Epizyotomi Episiotomy; Obstetric nursing